ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA PERMATA BAKERY DI SITUBINDO DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Yolanda, Mariska Anis; Arief, Mohammad Yahya; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
In business world, there are various ways to achieve success. Every businessman always learns how to make the business reach its target. The desired profit will encourage business people to achieve the determined targets. A businessman will keep on looking for opportunities for their company's marketing. Competition will keep happening, so opportunities must be seen and targets must be achieved. Therefore, Permata Bakery shop must be able to choose the right marketing strategy to develop and maintain the business stability because that becomes an indicator to get success. The purpose of this study is to analyze the factors that influence purchasing decisions at Permata Bakery in Situbondo with purchase intention as an intervening variable. The population in this research is the consumers of Permata Bakery shop. The sampling technique is determined by probability sampling. Data analysis and hypothesis testing use Partial Least Square - Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis testing using Smart PLS 3.0 application show that product quality has a significant effect on purchase intention, product quality has a significant effect on purchase decisions, word of mouth has a significant effect on purchase intention, word of mouth has a significant effect on purchase decisions, and purchase intention has an effect significant to the purchase decision. The results of the indirect effect hypothesis testing reveal that product quality variable has a significant positive effect on purchasing decisions through purchase intention. Word of mouth has a significant positive effect on purchasing decisions through purchase intention